2017
DOI: 10.1063/1.4979815
|View full text |Cite
|
Sign up to set email alerts
|

Flow reproducibility of whole blood and other bodily fluids in simplified no reaction lateral flow assay devices

Abstract: The "no reaction" lateral flow assay (nrLFA) uses a simplified LFA structure with no conjugate pad and no stored reagents. In the nrLFA, the capillary-based transport time or distance is the key indicator, rather than the outcome of a biochemical reaction. Hence, the calibration and reproducibility of the nrLFA device are critical. The capillary flow properties of several membrane types (nitrocellulose, nylon, cellulose acetate, polyethersulfone, and polyvinylidene difluoride) are evaluated. Flow rate evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…and contains a large quantity of cells, the membrane with short capillary rise time and large pore size will ensure a fast and uniform flow without potentially clogging the capillary passage. As reported 58 previously by our group, HF075 has a porosity of 82%, a pore size of 14.53 6 4.73 lm and a capillary rise time of 77 6 2 s/4 cm, which directly contributed to its excellent flow reproducibility 58 when using either anticoagulated or coagulation-activated blood.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…and contains a large quantity of cells, the membrane with short capillary rise time and large pore size will ensure a fast and uniform flow without potentially clogging the capillary passage. As reported 58 previously by our group, HF075 has a porosity of 82%, a pore size of 14.53 6 4.73 lm and a capillary rise time of 77 6 2 s/4 cm, which directly contributed to its excellent flow reproducibility 58 when using either anticoagulated or coagulation-activated blood.…”
supporting
confidence: 55%
“…57 We also demonstrated the excellent reproducibility of the nrLFA device and various related materials in the device fabrication. 58 Moreover, we conducted clinical trial using the nrLFA device with patients on warfarin therapy and successfully demonstrated the nrLFA's capability to monitor blood coagulation in conjunction with existing POC coagulation analyzers. 59 Existing POC coagulation analyzers are not widely affordable for everyday use due to the high initial cost and the per-use cost of the test strips.…”
mentioning
confidence: 99%
“…The amount of Pb existing in food samples can be estimated by drawing a straight line connecting each detection channel, a concept that is similar to that previously reported for albumin index evaluation [ 41 ]. When applying it to food matrices, it seems that the viscosity effects of food fluids influence the flow on a dPAD, in which a higher viscosity results in a slower rate [ 70 ], consequently affecting the color distance [ 71 ]. In our study, the supernatant obtained from the century egg extractions was rather viscous, which might have affected the color distance formation.…”
Section: Discussionmentioning
confidence: 99%
“…For this reasons, the diagnosis for MERS-CoV in human cases, sputum samples from the lower respiratory tract should be tested. However, the sputum is not applicable for the ICA, because the ICA is based on flow strip and requires low viscosity so that the antigen could transport through the strip ( 27 28 29 ).…”
Section: Discussionmentioning
confidence: 99%